Antibacterial Activity of Extracts and Essential Oils from Agathis bomeensis Resin - Ismail, Jusoh; Fouziah, Alet; Zaini, Assim; Fasihuddin, Badruddin Ahmad (Universiti Malaysia Sarawak, UNIMAS, 2011)
Studies on bioactivity of extracts and essential oils from resin of Agathis bomeensis were carried out. The antibacterial activity of A. bornensis extracts and essential oils were evaluated against five bacteria by agar diffusion method. The chemical constituents of the extracts and essential oils from the resin were analysed using gas chromatography-flame ionisation detector (GC-FID) and gas chromatography-mass spectrometer (GC-MS). Diameter of the inhibition zone of hexane extracts of A. borneensis resin varied from 8.7 to 10.0 mm. The largest zone of inhibition was obtained for Salmonella typhi (10 mm) and the lowest for Entrobacler aerogenes. Inhibition zones of dichloromethane extracts ranged from 8.7 to 11.1 mm. The largest zone of inhibition was obtained for Salmonella typhi (11.1 mm) whereas the lowest was for Staphylococcus aureus (8.7 mm). Chemical analyses showed that the most abundant constituents of the hexane and dicholomethane extracts were compounds from the phenolic, alcohol and terpene groups. The major phenolic compound was 2,4 di-tert-butylphenoi. The main alcohol groups detected include dodecanol, tetradecanol, pentadecanol, nonadecanol, docosanol and tetracosanol. The terpene group detected were limonene-1,2-diol, manoyl oxide, pimaric acid, (-)-terpinen-4-o1 and acampholenic aldehyde. Ethyl acetate and methanol extracts from the resin showed no significant activities. Hexane and dicholoromethane extractives obtained from A.bomensis resin showed weak to moderate antibacterial activities. Resin essential oils did not show any significant activity.